Excitation of Propagating Plasmons in Semi-Infinite Graphene Layer by Free Space Photons - 张磊 符秀丽 杨俊忠 (Communications in theoretical physics, 2014)
By investigating the diffraction of plane waves by a semi-infinite solution for propagating surface plasmons in graphene, which can be excited graphene edge. The theoretical results are confirmed by numerical simulations. excite propagating surface plasmons in graphene where the graphene edge plays graphene layer, we present a rigorous by incident plane waves through the Our results reveal a convenient way to an important role.